PERANCANGAN SISTEM INFORMASI BEASISWA DAN REKOMENDASI CALON PENERIMA BEASISWA BERBASIS WEB DI YAYASAN HIDUP MANDIRI AWALI SEMANGAT (HIMNAS) - Alirman Hulu; Mhd. Dicky Syahputra Lubis; Muhammad. Fauzi (Jurnal Widya, 2025)
The development of information technology has significantly impacted various fields, including education. The Hidup Mandiri Awali Semangat (HIMNAS) Foundation is an institution that provides scholarship programs for both outstanding and underprivileged students. However, the scholarship registration and selection process at HIMNAS is still conducted manually, leading to inefficiencies and data inaccuracies. This study aims to design and develop a web-based scholarship information system to facilitate the registration, selection, and recommendation of scholarship candidates. The research employs the Waterfall software development model, which includes stages such as requirements analysis, system design, implementation, testing, and maintenance. The result is a web-based information system that allows scholarship candidates to register online, upload documents, and track their verification status. Additionally, the system assists administrators in managing applicant data, conducting verification, and generating reports more quickly and accurately. The implementation of this system is expected to make the scholarship selection process at HIMNAS more transparent, efficient, and accessible. Keywords: Scholarship Information System, Scholarship Recommendation, Web, HIMNAS, Waterfall